(untitled) (ENTHYMEMA, 2013)
The first one-hundred pages of Giacomo Leopardi’s Zibaldone follow an organisation that differs from the structure held by the rest of the book. First of all, they are numbered but not dated. Secondly, their organisation is seemingly chaotic, though they proceed according a rigorous argumentation. The argumentative discourse is mostly structured around two cognitive modalities: following an analogical principle and proceeding through logical gaps connected by metaphors.